2021
DOI: 10.1093/cercor/bhaa391
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Functional Connectivity in Resting State: Assessment of the Dynamic Mean, Dynamic Variance, and Static Connectivity across Networks

Abstract: Recent efforts to evaluate the heritability of the brain’s functional connectome have predominantly focused on static connectivity. However, evaluating connectivity changes across time can provide valuable insight about the inherent dynamic nature of brain function. Here, the heritability of Human Connectome Project resting-state fMRI data was examined to determine whether there is a genetic basis for dynamic fluctuations in functional connectivity. The dynamic connectivity variance, in addition to the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 86 publications
3
24
0
Order By: Relevance
“…The heritability of functional connectivity (commonly quantified as the correlation of activity fluctuations between pairs of regions), has been studied using static (Colclough et al, 2017;Fornito et al, 2011;Fu et al, 2015;Glahn et al, 2010;Sinclair et al, 2015;Sudre et al, 2017) and dynamic fMRI (Barber et al, 2021), MEG (Colclough et al, 2017), and EEG (Schutte et al, 2013;Smit et al, 2008;van den Heuvel et al, 2013).…”
Section: Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The heritability of functional connectivity (commonly quantified as the correlation of activity fluctuations between pairs of regions), has been studied using static (Colclough et al, 2017;Fornito et al, 2011;Fu et al, 2015;Glahn et al, 2010;Sinclair et al, 2015;Sudre et al, 2017) and dynamic fMRI (Barber et al, 2021), MEG (Colclough et al, 2017), and EEG (Schutte et al, 2013;Smit et al, 2008;van den Heuvel et al, 2013).…”
Section: Heritabilitymentioning
confidence: 99%
“…Voxel-wise analyses of network functional connectivity estimated through spatial independent component analysis (ICA) (Barber et al, 2021;Fu et al, 2015;Glahn et al, 2010;Sudre et al, 2017;Yang et al, 2016) and seed-based connectivity (Adhikari et al, 2018) have demonstrated considerable genetic influence on several resting-state networks, including sensory (Fu et al, 2015) and transmodal association networks, ranging between 0.2<h 2 <0.8 (Adhikari et al, 2018;Barber et al, 2021;Glahn et al, 2010;Sudre et al, 2017;Z. Yang et al, 2016).…”
Section: Heritabilitymentioning
confidence: 99%
“…Although the recent studies have found atypical DFC in patients with ASDs, questions remain about the genetic mechanisms of higher DFC. Barber et al (2021) examined the heritability of rs-fMRI data of healthy young adults from the Human Connectome Project and found that heritability was moderate and tended to be higher for DFC than for SFC. Epidemiological studies have shown that patients with ASDs have high heritability, twin studies evaluating the heritability of ASDs showed high concordance rates (up to 90%) in monozygotic twins ( Freitag, 2007 ), and common genetic variations account for approximately 50% of the genetic risk for ASDs ( Gaugler et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The brain is complex and variable, and more studies have proved that the changes in FC across time help reveal dynamic changes in brain function. A growing number of fMRI studies have found dynamic FC that captures the time-sensitive information about dynamic brain network (Calhoun et al, 2014 ; Pervaiz et al, 2020 ; Barber et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%